2018
DOI: 10.1126/scitranslmed.aan8840
|View full text |Cite
|
Sign up to set email alerts
|

A PET imaging approach for determining EGFR mutation status for improved lung cancer patient management

Abstract: Tumor heterogeneity and changes in epidermal growth factor receptor (EGFR) mutation status over time challenge the design of effective EGFR tyrosine kinase inhibitor (TKI) treatment strategies for non-small cell lung cancer (NSCLC). Therefore, there is an urgent need to develop techniques for comprehensive tumor EGFR profiling in real time, particularly in lung cancer precision medicine trials. We report a positron emission tomography (PET) tracer, -(3-chloro-4-fluorophenyl)-7-(2-(2-(2-(2-F-fluoroethoxy) ethox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 33 publications
1
59
0
Order By: Relevance
“…Although KRAS and EGFR mutation profiling is critical in NSCLC management, some studies have raised issues with this approach (6,7). First, such mutation status captures only a small degree of tumor heterogeneity and does not provide a complete picture for the assessment of tumor characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Although KRAS and EGFR mutation profiling is critical in NSCLC management, some studies have raised issues with this approach (6,7). First, such mutation status captures only a small degree of tumor heterogeneity and does not provide a complete picture for the assessment of tumor characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…is one of such novel PET tracers with high specificity to activating EGFR mutant kinase. In NSCLC mice models, 18 F-MPG could reveal EGFR-activating mutations with high sensitivity and specificity (100). In 75 patients with NSCLC, patients with EGFR mutations had significantly higher 18 F-MPG uptake than did those with wild-type EGFR (100).…”
Section: Molecular and Functional Images For Precision Therapy In Nsclcmentioning
confidence: 99%
“…Epidermal growth factor (EGFR) -Tyrosine kinase inhibitor (TKI) treatment strategies for NSCLC depend on the mutation status of EGFR (72). A recent study by Sun et al demonstrated N-(3-chloro-4-fluorophenyl)-7-(2-(2-(2-(2-18F-fluoroethoxy) ethoxy) ethoxy) ethoxy)-6-methoxyquinazolin-4amine ( 18 F-MPG) PET/CT is a powerful method for precise quantification of EGFR-activating mutation status in NSCLC patients, and it is a promising strategy for noninvasively identifying patients sensitive to EGFR-TKIs and for monitoring the efficacy of EGFR-TKI therapy (72).…”
Section: Angiogenesis In Lung Cancermentioning
confidence: 99%